2002
DOI: 10.1063/1.1498476
|View full text |Cite
|
Sign up to set email alerts
|

Indirect evidence for strong nonadiabatic coupling in N2 associative desorption from and dissociative adsorption on Ru(0001)

Abstract: This paper reports the simultaneous internal state and translational energy resolved associative desorption flux of N 2 from Ru͑0001͒ using two different experimental approaches. Both experiments show that the nascent N 2 is formed with little vibrational excitation and that the total excitation in all N 2 degrees of freedom accounts for only 1 3 of the barrier energy. Roughly 2 3 of the energy necessary to surmount the barrier is lost to the surface in desorption. This behavior, as well as the unusual behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(113 citation statements)
references
References 66 publications
5
107
0
Order By: Relevance
“…The barrier V to reaction is much higher for N 2 Ru0001 (2 eV) [13] than for H 2 Cu (0:5 eV) [19]. In contrast to H 2 =Cu [17] comparison between adiabatic theory and experiment for N 2 reaction on Ru(0001) has so far presented major discrepancies, for dissociative chemisorption, associative desorption [11], and inelastic scattering [18], supporting the idea of a large influence of nonadiabatic effects.…”
Section: Multidimensional Effects On Dissociation Of N 2 On Ru(0001)mentioning
confidence: 77%
See 1 more Smart Citation
“…The barrier V to reaction is much higher for N 2 Ru0001 (2 eV) [13] than for H 2 Cu (0:5 eV) [19]. In contrast to H 2 =Cu [17] comparison between adiabatic theory and experiment for N 2 reaction on Ru(0001) has so far presented major discrepancies, for dissociative chemisorption, associative desorption [11], and inelastic scattering [18], supporting the idea of a large influence of nonadiabatic effects.…”
Section: Multidimensional Effects On Dissociation Of N 2 On Ru(0001)mentioning
confidence: 77%
“…Also, it has recently been shown that nonadiabatic [diabatic with [8] or without [9] couplings] models describe the dissociation of O 2 on Al(111) well, whereas an adiabatic description fails. It has even been argued that indirect evidence exists that nonadiabatic effects decrease the reactivity of N 2 on Ru(0001) (a low spin molecule with low electron affinity reacting on a general type transition metal surface) by more than an order of magnitude [10,11].…”
Section: Multidimensional Effects On Dissociation Of N 2 On Ru(0001)mentioning
confidence: 99%
“…15 Motivated by this controversy, an important number of theoretical methods that include electronic excitations have been recently developed. [16][17][18][19][20][21][22][23][24] In some cases, non-adiabatic dynamics based on low-dimensional calculations has resulted in overestimation of the effects associated with e-h pair excitations. For example, for N 2 /Ru(0001) it was claimed, 16 based on low-dimensional non-adiabatic calculations, that the huge discrepancy between low-dimensional adiabatic calculations and experiment was mostly due to e-h pair excitations, whereas a subsequent adiabatic high-dimensional dynamics study 25,26 showed that most of the discrepancy vanishes when the six degrees of freedom of the molecule are taken into account in the dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…All six nitrogen degrees of freedom are included in this study, while the positions of the surface atoms are frozen. The possible effect of electron-hole pairs 59 has not been included in the present description. In future work the effect of the motion of the Ru surface will be investigated.…”
Section: Introductionmentioning
confidence: 97%
“…52 Due to its importance, the N 2 -Ru system has been extensively studied experimentally. [53][54][55][56][57][58][59][60] Density-functional theory ͑DFT͒ calculations 52,61-65 explored the electronic structure and the reaction path.…”
Section: Introductionmentioning
confidence: 99%